Personalized management strategies in mast cell disorders: ECNM-AIM user’s guide for daily clinical practice : clinical management review - Valent, Peter; Hartmann, Karin; Schwaab, Juliana; Alvarez-Twose, Ivan; Brockow, Knut; Bonadonna, Patrizia; Hermine, Olivier; Niedoszytko, Marek; Carter, Melody C.; Hoermann, Gregor; Sperr, Wolfgang R.; Butterfield, Joseph H.; et al. (The journal of allergy and clinical immunology. In practice, 2022)
Mastocytosis is a myeloid neoplasm defined by expansion and focal accumulation of clonal mast cells (MCs) in one or more organs. The disease exhibits a complex pathology and may be complicated by MC activation, bone abnormalities, neurological problems, gastrointestinal symptoms, and/or hematologic progression. The World Health Organization divides mastocytosis into cutaneous forms, systemic mastocytosis (SM) and MC sarcoma. In most patients with SM, somatic mutations in KIT are detected. Patients with indolent SM have a normal to near-normal life expectancy, whereas patients with advanced SM, including aggressive SM and MC leukemia, have a poor prognosis. In those with advanced SM, multiple somatic mutations and an associated hematologic neoplasm may be detected. Mediator-related symptoms can occur in any type of mastocytosis. Symptoms may be mild, severe, or even life-threatening. In patients with severe acute symptoms, an MC activation syndrome may be diagnosed. In these patients, relevant comorbidities include IgE-dependent and IgE-independent allergies. Management of patients with SM is an emerging challenge in daily practice and requires in-depth knowledge and a multidisciplinary and personalized approach with selection of appropriate procedures and interventions. In this article, we review the current knowledge on SM and MC activation syndrome, with emphasis on multidisciplinary aspects in diagnosis and patient-specific management. In addition, we provide a user’s guide for application of markers, algorithms, prognostic scores, and treatments for use in daily practice.